A DETAILED OVERVIEW ON SOCIOLINGUISTIC COMPETENCE IN PEDAGOGICAL APPLICATIONS - Dedy Subandowo (Sanata Dharma University, 2022)
The purpose of this paper is to develop a general understanding of sociolinguistic competence in the pedagogical field. The discussion starts with an examination of communicative competence, which highlights some key components of communicative competence, as well as theoretical debates from experts. Following the discussion, there is an overview of sociolinguistic competence. Some linguists have developed a detailed explanation in this section, as well as the critical importance of distinguishing characteristic distinctions from other competences. The final section discusses how sociolinguistic competence can be applied in language pedagogy, such as academic writing and the roles of functional language in classroom discourses.